Transformational Leadership and Team Synergy in Improving Communication and Collaboration in Educational Settings - Agus Sutisna; Aah Khoriah; Juhartono; Efrita Norman (MES Bogor, 2024)
This study explores the impact of transformational leadership on team synergy, communication, and collaboration in educational environments. The purpose of the research is to examine how transformational leadership enhances team dynamics by fostering trust, communication, and participatory decision-making among teachers and staff. Utilizing a qualitative phenomenological methodology, in-depth interviews were conducted with school leaders, teachers, and administrative staff, complemented by participatory observation and document analysis. The results reveal that transformational leadership significantly improves collaboration by encouraging open communication and empowering team members to take initiative. Teachers reported feeling more motivated to innovate in their teaching methods and engage in interdisciplinary collaboration. However, challenges such as staff resistance and limited resources hindered the full adoption of collaborative practices in some schools. The study also highlights varying levels of team participation, which indicates that the effectiveness of transformational leadership depends on the leader's ability to engage all team members. The major conclusion of the study is that transformational leadership positively influences team synergy through enhanced trust and collaborative problem-solving. The findings provide important practical insights for educational leaders, suggesting that transformational leadership fosters a more inclusive and innovative school environment. This research contributes to the field by emphasizing the need for flexible leadership approaches that adapt to team dynamics and the critical importance of institutional support and resources to fully realize the benefits of transformational leadership in educational settings.